Value theory in environmental ethics and economics - Williams, Allison, author; McShane, Katie, advisor; Shockley, Kenneth, committee member; Fremstad, Anders, committee member (Colorado State University. Libraries, 2020)
The need for an environmental ethic is clear. Many in environmental ethics claim that an environmental ethic ought to be based on the intrinsic and/or non-anthropocentric value of nature, without consensus on a clear definition of those terms and without a clear analysis of the implications of adopting such an ethic. The purpose of this thesis is to first make sense of those different definitions and claims. Then, I describe Aldo Leopold's Land Ethic, a community-based environmental ethic outlined by Aldo Leopold, in order to contrast the different ways in which we ought to value the natural world with how we value things in economics. I argue that theories of value in economics, specifically existence value, are not compatible with nor can they capture the intrinsic, non-anthropocentric value of nature, and I propose an alternative ethic in opposition to the commodification of nature, and the relationship to the natural world formed by economics.